Prevalence and resistance profile of Escherichia coli isolated from urinary tract infections (Research, Society and Development, 2022)
The present study evaluated the prevalence and resistance profile of E. coli isolated from urinary tract infections. Methodology: This is an integrative review, carried out in different databases: CAPES Journal Portal, Virtual Health Library, National Library of Medicine and Online Scientific Electronic Library, of articles published in the last 5 years (2016-2020), using the following descriptors: E. coli, urinary infection and resistance. 86 were collected for screening, however, adopting the inclusion and exclusion criteria, 6 articles were selected. Studies have shown that E. coli is the most common pathogen in UTIs, its prevalence in most studies being greater than 50%. Furthermore, in all studies, females were more affected. As for the susceptibility profile of E. coli, it was found that the strains showed a high resistance profile against β-lactam drugs (Ampicillin and Amoxicillin) and sensitivity against drugs of the class of fluoroquinolones and aminoglycosides. The occurrence of pathogens that cause urinary tract infections vary geographically, as does their susceptibility profile, therefore, it is necessary to carry out studies that assess this scenario in order to avoid the indiscriminate use of antimicrobials.